2013
DOI: 10.1016/j.geomorph.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Erosion in Mediterranean landscapes: Changes and future challenges

Abstract: Intense erosion processes are widespread in the Mediterranean region, and include sheet wash erosion, rilling, gullying, shallow landsliding, and the development of large and active badlands in both subhumid and semi-arid areas. This review analyses the main environmental and human features related to soil erosion processes, and the main factors that explain the extreme variability of factors influencing soil erosion, particularly recent land use changes. The importance of erosion in the Mediterranean is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
158
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(178 citation statements)
references
References 149 publications
(113 reference statements)
5
158
0
5
Order By: Relevance
“…The topsoil of the studied vineyard was rather vulnerable to aggregate breakdown in both 264 treatments (Figure 3), as often observed in hilly areas of the Mediterranean, where OC contents as 265 low as 20 g kg -1 are not unusual (Jones et al 2005) due to erosion (García-Ruiz et al 2013;Novara 266 et al 2015) and poor soil development (Novara et al 2015). Moreover, deep tillage before vine 267 planting could have also contributed to reducing OC contents due to the combined effects of (i) 268 mixing of deep horizons with the topsoil, as often happens after severe disturbances (e.g., Stanchi et 269 al.…”
Section: Discussion 257mentioning
confidence: 69%
“…The topsoil of the studied vineyard was rather vulnerable to aggregate breakdown in both 264 treatments (Figure 3), as often observed in hilly areas of the Mediterranean, where OC contents as 265 low as 20 g kg -1 are not unusual (Jones et al 2005) due to erosion (García-Ruiz et al 2013;Novara 266 et al 2015) and poor soil development (Novara et al 2015). Moreover, deep tillage before vine 267 planting could have also contributed to reducing OC contents due to the combined effects of (i) 268 mixing of deep horizons with the topsoil, as often happens after severe disturbances (e.g., Stanchi et 269 al.…”
Section: Discussion 257mentioning
confidence: 69%
“…In WY14, far less accumulated, 8.3 Â 10 4 kg, but the runoff sediment load was 2 g/L, similar to WY15. Although runoff sediment loads were modest, the annual sediment yield of the drainage area, 120e735 Mg/km 2 , is in the middle range of values from other agriculturally developed regions (Koluvek et al, 1993;de Vente and Poesen, 2005;Ficklin et al, 2010;García-Ruiz et al, 2013). Grain size analyses showed that accumulating sediment had a different texture from both upland soil available for transport and subsurface soil in the infiltration basin.…”
Section: Sediment Transport and Accumulationmentioning
confidence: 89%
“…It causes the loss of agricultural productivity and a decline of water quality [2][3][4]. It is estimated that about 10 million ha of cropland is lost in the world due to soil erosion every year [5] and is often a common occurrence in the Mediterranean and China [6,7]. Erosion rates vary throughout the world: In the hilly areas of the northern Mediterranean region, along the Atlantic coastline and stretching from France to Greece, the annual sediment losses are in the order of 1.5 Mg ha −1 y −1 [8].…”
Section: Introductionmentioning
confidence: 99%